The impact of EEG biofeedback training on the athletes’ motivation and bench press performance - Prończuk, Magdalena; Chamera, Tomasz; Markowski, Jarosław; Pilch, Jan; Smólka, Wojciech; Zajac, Adam; Maszczyk, Adam (Biology of Sport, 2024)
The objective of this paper was to determine the impact of EEG-biofeedback training on the motivation and efficiency of powerlifters during the bench press exercise in relation to the external load and the level of training. The study included 18 trained powerlifters who were divided into the intermediate (IG) and the advanced (AG) groups. EEG-biofeedback training was conducted every three days, lasting 27 minutes each time (5×3-minute intervals with recovery periods – lying on a bench – between them 4×3 minutes), and ended with a final EEG measurement in the second cycle of research. The repeated measures ANOVA showed intra group differences due to external loading for the FAI (Frontal Alpha Asymmetry) obtained in the EEG both before and after biofeedback training. In AG group analysis revealed significant differences between 65%1RM and 35%1RM. In the IG group between 35%1RM and 50, 65 and 80%1RM. One of the major variables influencing the efficiency of strength training, including bench press workouts, is the level of training. The more successfully an athlete uses motivation when exercising, the better their training, which translates into greater results and a lower chance of injury.